The stellar debut of Galactica MacFee [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- 44 Scotland Street series, 2024)
"Angus Lordie is approached in the park by a shadowy, Deep Throat like figure with government secrets to share, who mistakes him for a journalist. Now Angus is privy to some controversial plans of the Scottish Parliament -- but just what is he meant to do about it? Elsewhere, Big Lou's husband Bob hires a personal trainer who changes his entire outlook on life, much to Lou's dismay. At the schoolhouse, young Bertie Pollock's class has a new ringleader, Galactica MacFee, who quickly comes between Bertie and Olive. All this proves too much for Bertie to bear, and he flees to Glasgow with best friend Ranald Braveheart MacPherson in tow. And the indomitable Irene again finds herself in Edinburgh . . . and it looks like there might be romance in the air. Meanwhile, Matthew, too, is keeping busy. He's thinking of investing in the brand new Pictish Experience Centre, meant to allow residents to experience what life was like for Scotland's mysterious early people, the Picts. And they may have made a fantastic discovery -- the earliest known work of Scottish literature! But what exactly do those mysterious Pictish runes say?"--